Anneal Temperature Effect on Crystallite Size and Electric Conductivity of LiMn2O4 - Khairul Basar; Xianglian Xianglian; Sainer Siagian; Kouta Ohara; Takashi Sakuma; Haruyuki Takahashi; Osami Abe; Naoki Igawa; Yoshinobu Ishii (Institut Teknologi Bandung, 2009)
Powder samples of LiMn2O4 have been prepared by solid state reaction of LiOH and MnO2. Neutron scattering experiments at room temperature and conductivity measurement have been performed on the samples. Anneal temperature effect on the crystallite size and electric conductivity of LiMn2O4 is analyzed. The average crystallite size is obtained from the full width at half maximum (FWHM) of Bragg lines using Scherrer equation. The average crystallite size increases with the increase of anneal temperature. Activation energy and conductivity prefactor increase with anneal temperature.